Serious Adverse Drug Reactions in Children and Adolescents Treated On- and Off-Label with Antidepressants and Antipsychotics in Clinical Practice - Egberts, Karin M.; Gerlach, Manfred; Correll, Christoph U.; Plener, Paul L.; Malzahn, Uwe; Heuschmann, Peter; Unterecker, Stefan; Scherf-Clavel, Maike; Rock, Hans; Antony, Gisela; Briegel, Wolfgang; Fleischhaker, Christian; Häge, Alexander; Hellenschmidt, Tobias; Imgart, Harmut; Kaess, Michael; Karwautz, Andreas; Kölch, Michael; Reitzle, Karl; Renner, Tobias; Reuter-Dang, Su-Yin; Rexroth, Christian; Schulte-Körne, Gerd; Theisen, Frank M.; Walitza, Susanne; Wewetzer, Christoph; Fekete, Stefanie; Taurines, Regina; Romanos, Marcel (Pharmacopsychiatry, 2022)
Introduction Despite the growing evidence base for psychotropic drug treatment in pediatric patients, knowledge about the benefit-risk ratio in clinical practice remains limited. The ‘Therapeutic Drug Monitoring (TDM)-VIGIL’ study aimed to evaluate serious adverse drug reactions (ADRs) in children and adolescents treated with antidepressants and/or antipsychotics in approved (‘on-label’), and off-label use in clinical practice.Methods Psychiatric pediatric patients aged 6-18 years treated with antidepressants and/or antipsychotics either on-label or off-label were prospectively followed between October 2014 and December 2018 within a multicenter trial. Follow-up included standardized assessments of response, serious ADRs and therapeutic drug monitoring.Results 710 youth (age=14.6±2.2 years, female=66.6%) were observed for 5.5 months on average; 76.3% received antidepressants, 47.5% antipsychotics, and 25.2% both. Altogether, 55.2% of the treatment episodes with antidepressants and 80.7% with antipsychotics were off-label. Serious ADRs occurred in 8.3% (95%CI=6.4–10.6%) of patients, mainly being psychiatric adverse reactions (77.4%), predominantly suicidal ideation and behavior. The risk of serious ADRs was not significantly different between patients using psychotropics off-label and on-label (antidepressants: 8.1% vs. 11.3%, p=0.16; antipsychotics: 8.7% vs 7.5%, p=0.67). Serious ADRs occurred in 16.6% of patients who were suicidal at enrollment versus 5.6% of patients who were not suicidal (relative risk 3.0, 95%CI=1.9-4.9).Conclusion Off-label use of antidepressants and antipsychotics in youth was not a risk factor for the occurrence of serious ADRs in a closely monitored clinical setting. Results from large naturalistic trials like ours can contribute to bridging the gap between knowledge from randomized controlled trials and real-world clinical settings.
Keywords: antidepressants; antipsychotics; child; adverse drug reactions; safety